Surveillance of Rodent Pests for SARS-CoV-2 and Other Coronaviruses, Hong Kong - Elliott F. Miot; Brian M. Worthington; Kar Hon Ng; Lucy de Guilhem de Lataillade; Mac P. Pierce; Yunshi Liao; Ronald Ko; Marcus H. Shum; William Y. Cheung; Edward C. Holmes; Kathy S. Leung; Huachen Zhu; et al. (Emerging Infectious Diseases, 2022)
We report surveillance conducted in 217 pestiferous rodents in Hong Kong for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We did not detect SARS-CoV-2 RNA but identified 1 seropositive rodent, suggesting exposure to a virus antigenically similar to SARS-CoV-2. Potential exposure of urban rodents to SARS-CoV-2 cannot be ruled out.